REVIEW ON USAGE OF MEDICINAL PLANTS IN FISH DISEASES - K. SHANKAR MURTHY; B.R.KIRAN (International Journal of Pharma and Bio Sciences, 2013)
The purpose of present review is to enlighten the present and future prospective on importance of medicinal plants on fish diseases. Now a day, the parasitic outbreak acts as an important limiting factor for fish culture. The infection of Trichodina parasites and Aeromonas hydrophila bacterium has lead to great economic loss for fish culture business. These fast antibiotics from plants are frequently used to control fish diseases. The current review article provides an account of phytochemicals, immunostimulants, phytobiotics, fermented Vegetable product (FVP) and other plant extract in fish disease control and management.